Study protocol: Dental and periodontal characteristics of older adults in Atahualpa, Ecuador within the Atahualpa Project cohort - Marcelo Armijos Briones; Patricia Estefanía Ayala Aguirre; Pablo Lenin Benitez Sellan; Antonio Lanata-Flores; Oscar Marcillo-Toala; Denisse A. Rumbea; Robertino M. Mera; Oscar H. Del Brutto (PLoS ONE, 2026)
This study protocol describes an observational, cross-sectional investigation of oral health in community-dwelling older adults from Atahualpa, a rural village in Ecuador, embedded within the long-standing Atahualpa Project cohort. Using a door-to-door survey approach, all registered residents aged ≥60 years (n = 410) will be invited to participate. Participants will attend twice weekly at the School of Dentistry of University through six coordinated stations: The first station will include a general oral diagnosis and the collection of general participant data using the unique Atahualpa project identifier. The second station will record the periodontal clinical examination according to the AAP/EFP 2018 clinical guidelines. In addition, subgingival biofilm sampling will be performed for 16S rRNA sequencing and gingival crevicular fluid for multiplex cytokine profiling. The third station will obtain high-resolution digital models through an intra-oral scanning (IOS) for dental morphometrics. The fourth station will record a cone-beam computed tomography (CBCT) to support periodontal charting, and complementary structural findings. The fifth station will indicate dental treatments: restorations, root canals, extractions, and prosthesis using computer-aided design and computer-aided manufacturing (CAD/CAM). Finally, the last station will perform an oral health education: oral health promotion and structured questionnaires such as the Geriatric Oral Health Assessment Index (GOHAI), the European Health Literacy Survey-16 (HLS-EU-Q16) (in its Spanish version) and the Short Health Literacy Screen (BHLS). Primary objectives are to quantify associations between periodontitis severity, microbial composition, and local inflammatory profiles with neurocognitive and neuroimaging outcomes already available in the cohort (total MoCA and a composite cerebral small vessel disease score), controlling. Therefore, this protocol addresses the research question of whether, in older adults residing in the Atahualpa community, greater periodontitis severity is associated with lower neurocognitive performance and a higher burden of cerebral small vessel disease on neuroimaging within the existing cohort. It also examines whether the composition of the subgingival microbiome and cytokine profiles in gingival crevicular fluid correlate with periodontal severity and are related to these cerebral outcomes. Furthermore, it describes three-dimensional dental morphology (including features derived from ASUDAS for comparison with published Pima frequencies) to clarify whether there is similarity between the two ethnic groups.